Synergistic effects of Thymus vulgaris essential oil in combination with antifungal agents and inhibition of virulence factors of Candida albicans - Blanc, Alan Roy (2023)
Background: Combination antifungal therapy has become a prominent approach in medical practice as it takes advantage of synergistic interactions by interfering with multiple targets of the pathogen, broadening the spectrum of activity, reducing the development of resistance, and improving treatment outcomes. Therefore, combining conventional antifungal drugs with natural products can increase antifungal activity, reduce side effects, and optimize therapeutic effects. Purpose: The present study aimed to evaluate the antifungal activity of thyme essential oil (ThyEO) in combination with amphotericin B, caspofungin, fluconazole, itraconazole, and posaconazole (PSZ), as well as its inhibitory effect on Candida albicans virulence factors. Materials and Methods: The microbroth dilution assay was employed to determine the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC). Interactions were assessed using the microdilution checkerboard assay. Ergosterol and methylene blue assays were used to detect effects on fungal membrane, while the sorbitol assay was used to detect effects on fungal cell wall. Inhibition of yeast virulence factors (adherence to epithelial cells, germ tube and pseudomycelium formation, secretion of hydrolytic enzymes, and biofilm formation) was assessed with previously reported methods. Results: Almost all combinations showed additivism against C. albicans, except ThyEO/PSZ (31.25/0.0039 µg/ml), which showed partial synergism. Furthermore, all mixtures were fungicidal against C. albicans strains. ThyEO/PSZ, its components alone, and thymol were shown to disrupt the fungal cytoplasmic membrane, increasing its permeability. ThyEO/PSZ, at sub-inhibitory concentrations, significantly decreased the ability of C. albicans to adhere to buccal epithelial cells. ThyEO/PSZ, ThyEO, and PSZ were able to reduce the pseudomycelium production of C. albicans while thymol completely inhibited its formation. ThyEO/PSZ, each combination component on its own, and thymol inhibited biofilm formation and preformed biofilm of C. albicans. Notably, ThyEO/PSZ showed synergistic and fungicidal activity against a resistant strain of C. albicans, reducing the PSZ dose by 4-fold. Conclusion: These findings make ThyEO and ThyEO/PSZ mixture valuable candidates for the development of alternative antifungals with a lower incidence of adverse effects.